2020
DOI: 10.21203/rs.3.rs-39726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection and prevalence of depression among adult type 2 diabetes mellitus patients attending non-communicable diseases clinics in Lilongwe, Malawi

Abstract: Abstract Background Depression is associated with chronic physical illnesses and negatively affects health outcomes. However, it often goes undiagnosed and untreated. We investigated the prevalence of depression among adult type 2 diabetes mellitus (T2DM) patients attending non-communicable diseases (NCD) clinics in Lilongwe, Malawi, and estimated the level of routine detection by NCD clinicians. This study set out to determine the prevalence of major depression and it… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our study had also reported that among those with major depressive disorder, most clients (52%) had moderate depressive symptoms indicated by higher PHQ scores. This was worrisome as it showed most patients were unattended to in time while symptoms were advancing and this could impact negatively on their general health status [8].The current study had also reported higher proportions of sub-threshold depressive disorder of 43% which was twice higher than that reported among type 2 diabetes in Malawi as well as among patients with cancer elsewhere [20,24]. This group of patients in our study presented with clinically signi cant depressive symptoms without meeting the criteria for major depressive disorder at cut-off value of 9 on PHQ-9 score.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Our study had also reported that among those with major depressive disorder, most clients (52%) had moderate depressive symptoms indicated by higher PHQ scores. This was worrisome as it showed most patients were unattended to in time while symptoms were advancing and this could impact negatively on their general health status [8].The current study had also reported higher proportions of sub-threshold depressive disorder of 43% which was twice higher than that reported among type 2 diabetes in Malawi as well as among patients with cancer elsewhere [20,24]. This group of patients in our study presented with clinically signi cant depressive symptoms without meeting the criteria for major depressive disorder at cut-off value of 9 on PHQ-9 score.…”
Section: Discussionmentioning
confidence: 61%
“…This might be the true estimate considering that we used active screening approach other than self-reports. However, we expected the prevalence to be even higher than reported considering previous estimates [19,20]. The lower-than-expected estimate could be explained by excluded cases of physical and emotional distress which would have had scored high on PHQ-9 score and increase the prevalence of major depressive disorder.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations